Pregnancy and childbirth outcomes among indigenous adolescents in Guatemala: a cohort study - Noe Gómez; Odette Del Risco Sánchez; Maira Pinho-Pompeu; Helymar Machado; Luis Bahamondes; Fernanda Surita (BMC, 2022)
Plain Language Summary This study aims to evaluate the sociodemographic characteristics and outcomes associated with pregnancy in Indigenous adolescents and compare them to other women who gave birth in a public hospital in Guatemala. We conducted a retrospective cohort study on four groups: Indigenous adolescents, Nonindigenous adolescents, Indigenous adults, and Nonindigenous adults. Subsequently, we compared the sociodemographic characteristics of the latter three groups with those of the Indigenous adolescents to evaluate whether being in this age group in combination with belonging to an Indigenous ethnic group increased unfavorable outcomes during pregnancy, childbirth, and postpartum. We observed that Indigenous adolescents have limited academic opportunities compared with Nonindigenous adolescents; the usage of contraceptive methods was lower in adolescents (Indigenous and non-Indigenous), and unplanned pregnancies were more frequent in Indigenous adolescents than in Nonindigenous adolescents and adults), and a high percentage of all women did not attend antenatal care. We analyzed obstetric practices during childbirth, and a high incidence of episiotomies was reported in both groups of adolescents (42.5% for Indigenous women and 38.8% for Nonindigenous women). Newborns of Nonindigenous adolescents had a higher frequency of low birth weight. Our study provides an overview of the characteristics of pregnancy among different age groups, findings that could be used to develop targeted interventions for each group and create public policies that would provide equal opportunities for all women while also ensuring a healthy pregnancy.